DEVELOPING HIGHER ORDER THINKING SKILL TEST INSTRUMENT FOR THE 10TH GRADE ENGLISH MATERIAL AT MA MADANI ALAUDDIN PAO-PAO - Mardiana Mardiana; Nur Asik; Eril Sandi; St. Aminah Putri Abdullah (International Conference on Social and Islamic Studies, 2021)
The purpose of this study is to develop HOTS items in the English material, to determine the level of validity of the items, to determine the reliability of the items for class X in MA Madani Alauddin Pao-Pao. The type of this research is research and development (R&D). The development model used is this research is the Plomp modelwhich consists of five stages of development, namely Preliminary investigation, Design, Realization/Construction, Test, Evaluation and Revision (Test, Evaluation and Revision), and Implementation (Implementation). The subjects in this study are students at class X MIA 2 in MA Madani Alauddin Pao-Pao. The instruments used in data collectionare validation sheets and HOTS items. Based on the results of the study, it is obtained that the level ofvalidity of the HOTS items was 3.7 which is in the very valid category, the reliability of the HOTS items is 0.81 which is in very good category and thedifficulty level of the HOTS items is 0.60 which is in the medium category. The implications of the developing HOTS items can train and encourage students to do high-level reasoning so that they are not fixated on the pattern of answers that result from the memorization process without knowing the concept of knowledge, and it can make students thinkcritically in doing the test. So that the answers can be produced based on in-depth reasoning from the questions for each item, namely 100 multiplechoice questions and 50 essay questions.